Premenstrual syndrome – greater risk of menopausal symptoms - Wilamowska, Agnieszka (Menopause Review/Przegląd Menopauzalny, 2006)
Premenstrual syndrome (PMS) is quite prevalent among women of reproductive age. PMS decrease in the transition to menopause. Women who report PMS are at greater risk of menopausal hot flashes, poor sleep, depressed mood and decreased libido. A history of PMS is the main predictor for climacteric symptoms. The studies are needed to explain symptom physiopathology and aid in the effective treatments for women.